INCLUSION PERCEPTION BY AUTISTIC ACADEMIC STUDENTS (CIPEEX, 2022)
AUTISM SPECTRUM DISORDER (ASD) IS DEFINED AS A COMPLEX DISORDER OF THE NEUROLOGICAL SYSTEM, CHARACTERIZED FOR INTERACTION AND SOCIAL BEHAVIOR IMPAIRMENT. IN ADDITION TO A STRICT REPERTOIRE OF INTERESTS AND ACTIVITIES. DURING THE AUTISTIC€™S STUDY LIFE, THESE PEOPLE FACE MANY ADVERSITIES WHICH PREJUDICE THEIR INTEGRATION AND STUDY CONTINUITY. IN THE UNIVERSITY, THIS REALITY IS NO DIFFERENT FROM THE EARLY STUDIES, CHALLENGES HAPPEN EVERY TIME. THESE CHALLENGES CREATE BARRIERS TO THEIR ADAPTATION IN THIS NEW ENVIRONMENT. DUE TO THIS, IT IS IMPORTANT A SET OF ACTIONS AND SERVICES TO PROVIDE INCLUSION FOR UNIVERSITY STUDENTS IN THE SPECTRUM. THUS, THE ARTICLE€™S PURPOSE IS TO CONTRIBUTE TO A BETTER UNIVERSITY EXPERIENCE FOR AUTISTIC PEOPLE IN UNIVERSIDADE EVANGÉLICA DE GOIS - UNIEVANGLICA. THIS METHOD OF STUDY IS CHARACTERIZED AS QUALITATIVE. THE PLACE WHERE WAS ACCOMPLISHED THIS STUDY IS UNIVERSIDADE EVANGÉLICA DE GOIS - UNIEVANGLICA. THE SAMPLE WAS FOUR AUTISTIC STUDENTS AGED 18 OR OVER FROM MEDICINE SCHOOL. THE RESEARCH COLLECTION WAS FROM THE USE OF QUESTIONS ABOUT HOW THEY FEEL INCLUDED IN THE UNIVERSITY AND QUESTIONS ABOUT SPECIAL ADAPTATIONS TO THEIR NEEDS. THEN, THE OUTCOMES REACH THE PROSPECT THAT THE STUDENTS DO NOT FEEL VERY INCLUDED. ACADEMIC AND SOCIAL CHALLENGES FACED BY AUTISTIC STUDENTS MIGHT BE RELATED TO ASD SYMPTOMS, SUCH AS SPEAK IN PUBLIC, DIFFICULTIES IN SOCIAL RELATION WITH OTHER STUDENTS, COLLEGE PLACES WITH MANY SENSORIAL STIMULI. THEREFORE, BASED ON THE OUTCOMES, THERE WERE SOME INCLUSION ACTIONS, HOWEVER NOT ALL THE ACTIONS WERE EFFECTIVE OR HAPPENED IN THE IDEAL WAY.